2013
DOI: 10.1785/0120120336
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Cleburne, Texas, Earthquake Sequence from June 2009 to June 2010

Abstract: On 9 June 2009, an M bLg 2.8 earthquake shook Cleburne, Texas, a community not known to have previously experienced earthquakes. Over 50 small earthquakes followed by the end of December 2009. A temporary network of four and then five IRIS-Passcal broadband systems was deployed from June 2009 to June 2010, recording data that were used to locate 38 events with the most confident P-and S-arrival picks. Event locations were distributed along a 2 km long north-northeast trend. The location centroid was at 32.298°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…The above observations demonstrate that the Timpson earthquakes share many features in common with recent earthquakes elsewhere in the Midwestern U.S. that have been inferred to be triggered or induced. Like the 1962–1968 earthquakes in Denver [ Healy , et al ., ; Herrmann and Park , ], the 2008–2009 earthquakes in Dallas‐Fort Worth [ Frohlich et al ., ], the 2009 earthquakes near Cleburne, TX, [ Justinic et al ., ] and the 2011 earthquake in Youngstown, OH [ Kim , ], the Timpson earthquakes are the first known earthquakes in this location and began only after injection began. As in Denver, Dallas‐Fort Worth, Cleburne, 2011 in Arkansas [ Horton , ], and 2011 in Youngstown OH [ Kim , ], the Timpson earthquakes had focal depths at or exceeding the depths of injection and occurred along a linear trend situated within only a few kilometers of the site of injection.…”
Section: Discussionmentioning
confidence: 99%
“…The above observations demonstrate that the Timpson earthquakes share many features in common with recent earthquakes elsewhere in the Midwestern U.S. that have been inferred to be triggered or induced. Like the 1962–1968 earthquakes in Denver [ Healy , et al ., ; Herrmann and Park , ], the 2008–2009 earthquakes in Dallas‐Fort Worth [ Frohlich et al ., ], the 2009 earthquakes near Cleburne, TX, [ Justinic et al ., ] and the 2011 earthquake in Youngstown, OH [ Kim , ], the Timpson earthquakes are the first known earthquakes in this location and began only after injection began. As in Denver, Dallas‐Fort Worth, Cleburne, 2011 in Arkansas [ Horton , ], and 2011 in Youngstown OH [ Kim , ], the Timpson earthquakes had focal depths at or exceeding the depths of injection and occurred along a linear trend situated within only a few kilometers of the site of injection.…”
Section: Discussionmentioning
confidence: 99%
“…Wastewater injection is associated with all of the largest injection-induced earthquakes (Horton, 2012;Frohlich et al, 2014;Keranen et al, 2014;Rubinstein et al, 2014), and there are many more reported cases of wastewater injection-induced earthquakes in the past five years in the United States alone (Frohlich et al, 2011(Frohlich et al, , 2014Frohlich, 2012;Justinic et al, 2013;Kim, 2013;Block et al, 2014;Keranen et al, 2014), and yet there are only approximately 35,000 wastewater disposal wells that are active in the United States. This is in contrast to hydraulic fracturing, which is far more common (∼1:8 million treatments over ∼1 million wells, 1947-2010 in the United States; Gallegos and Varela, 2014) than wastewater disposal wells, and yet there are only three reported cases of hydraulic fracturing-induced earthquakes in the United States (Holland, 2013;Friberg et al, 2014;Skoumal et al, 2015) and only a few more worldwide (BC Oil andGas Commission, 2012, 2014;Green et al, 2012;Farahbod et al, 2015).…”
Section: Which Methods Of Fluid Injection Has the Highest Likelihood Omentioning
confidence: 99%
“…The largest reported magnitude was m bLg 3.5 for an earthquake on 24 June 2012. Scientists at SMU installed a five-station temporary network to record this activity (Justinic et al, 2013) and were able to locate accurately 38 earthquakes occurring along a 2-3-km-long north-south-trending linear feature, with bestdetermined focal depths of 3.5-4.2 km. The centroid of these locations was 1.3 km from a saltwater disposal well that began injecting in 2007 at depths of 2.4-3.1 km, and 3.2 km distant from a well that injected at depths of 3.2-3.3 km from September 2005 through July 2009.…”
Section: Cleburne 2009-2012: Almost Certainly Inducedmentioning
confidence: 99%